DESIGN, TECHNOLOGY AND CONTEMPORARY DANCE CASE STUDY OF CONTEMPORARY DANCE WORKS TALE TALE SCENOGRAPHY DESIGNER'S PERSPECTIVE - Sara, Cindy Fadhila (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
This research raises a case study of the contemporary dance work Tale Tale by choreographer Sherli Novalinda, a contemporary work rooted in body archives and tales which is an oral tradition of the ancestors of the Kerinci community. This work combines traditional elements executed with a contemporary style to create a dialogue between dance art, design, and technology. The main focus of the research is to reconstruct the scenography from the perspective of a designer who plays a role in designing a dynamic stage space that not only supports the movements of the dancers but also reinforces the messages and emotions that the choreographer wants to convey. Using a qualitative approach and case studies, this study explores the creative process behind scenography design and the application of technology in Tale Tale's contemporary dance works. Technologies such as animation and visual projection are used as iterative elements that respond to dance movements in real-time, creating an immersive visual experience for the audience. The results of this study show that the collaboration between design, technology, and contemporary dance not only enriches the expression of movement, but also enriches the living space, where dancers and audiences are emotionally and visually involved, and can create a more interactive, deep, and meaningful art experience. This researcher emphasized that the synergy between design, technology, and contemporary dance can enrich the aesthetic dimension of performing arts. This study is expected to be a reference for the development of innovative scenography designs, as well as encourage further exploration in cross-disciplinary collaboration in the field of performing arts.